Interpretive Research and its Use in the Field of Pedagogy - Krmac, Nina (Revija za elementarno izobraževanje, 2022)
The article focuses on the definition of interpretive research, which is relatively unfamiliar within Slovenia. Other parts of the world also lack a common definition, and various authors classify it differently. Some authors define it as a research method within the interpretive paradigm, whereas others describe it as a type of research or a way of interpreting data that can also be applied within other paradigms. It is often equated with qualitative research. The article presents its role and importance in research, with particular emphasis on its utility in the field of pedagogy.
Keywords: interpretive research, education, research paradigms, quantitative research, qualitative research